ESR investigation of the low temperature state in alpha-(BEDT-TTF)(2)KHg(SCN)(4) - Semeno, A; Singleton, J; Ardavan, A; Schrama, M; Kurmoo, M; Day, P (Elsevier, 1999)
We have performed ESR measurements on an alpha-(BEDT-TTF)(2)KHg(SCN)(4) Single crystal at temperatures down to 0.9 K. Two regions where the ESR intensity decreases were observed. One corresponds to the proposed SDW transition (T approximate to 9 K); the other takes place at T less than or equal to 2 K. A new resonance line appears below the transition temperature T approximate to 9 K; its intensity grows continuously as the temperature is lowered. We regard the decrease of the ESR line at very low temperatures as evidence of a further phase transition.